PENGARUH HUKUM WARIS ISLAM DALAM MASYARAKAT BETAWI DI RT 03 dan 04 RW 07 KELURAHAN HARAPAN MULYA JAKARTA PUSAT: Influence Of Islamic Inheritance Law In Betawi Society In RT 03-04 RW 07 Harapan Mulya Vilage, Central Jakarta - Sashika Fawwaz Zayyan; Bakri, Khairani (Faculty of Law, Universitas Trisakti, 2025)
Inheritance law governs the transfer of rights and obligations from a deceased person to their heirs. In Indonesia, there are three inheritance systems: customary law, Islamic law, and Western civil law. Each system has different principles and procedures, which may lead to legal conflicts. In the Betawi community, particularly in RT 03 and 04 RW 07, Harapan Mulya, Central Jakarta, an interesting phenomenon occurs. Although the Betawi people are known for their strong adherence to Islamic teachings, inheritance practices often show complex dynamics. The main issue is: how much does Islamic inheritance law influence this community? In practice, inheritance is not always distributed according to Islamic law, which states that a male receives twice the share of a female, as written in Surah An-Nisa verse 11. Even though the community holds Islamic values, many families choose to divide inheritance equally or based on family agreement. In conclusion, Islamic inheritance law does not fully influence inheritance practices in the Betawi community of RT 03 and 04 RW 07, as many prefer customary distribution based on equality and family harmony